Unique features of different members of the human guanylate-binding protein family - Tripal, Philipp; Bauer, Michael; Naschberger, Elisabeth; Mörtinger, Thomas; Hohenadl, Christine; Cornali, Emmanuelle; Thurau, Mathias; Stürzl, Michael (Journal of Interferon and Cytokine Research, 2007)
Guanylate-binding proteins (GBPs) are the most abundant cellular proteins expressed in response to interferon-γ (IFN-γ), with seven highly homologous members in humans, termed HuGBP-1 to HuGBP-7. To date, differential features that may indicate differential functions of these proteins have not been described. Here, we investigated the expression and subcellular localization of the different HuGBPs in endothelial cells (EC). IFN-γ, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) induced the expression of HuGBP-1, HuGBP-2, and HuGBP-3 at similar high levels. In contrast, expression of HuGBP-4 and HuGBP-5 was robustly induced only by IFN-γ and not by TNF-α and IL-1β. Expression of HuGBP-6 and HuGBP-7 was not detected in EC under the various conditions examined. Investigating subcellular localization of the EC-expressed HuGBPs, HuGBP-1, HuGBP-3, and HuGBP-5 were exclusively detected in the cytoplasm, whereas HuGBP-2 and HuGBP-4 displayed a nucleocytoplasmic distribution. Treatment of the cells with IFN-γ and aluminum fluoride caused rapid enrichment of HuGBP-1 and HuGBP-2 in the Golgi apparatus, as demonstrated by time-lapse microscopy and fluorescence analyses of GFP-tagged HuGBPs. HuGBP-3 and HuGBP-4 were never detected in the Golgi apparatus, whereas HuGBP-5 was constitutively enriched in this cytosolic compartment, irrespective of stimulation. These results assign a characteristic pattern of expression and subcellular localization to each of the HuGBPs, indicating for the first time that these proteins may have different cellular functions. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up